Impact of Sales Growth, Profitability, Liquidity, and Size on Firm Value in the Automotive Sector - Ambri, I Ketut Hardy Putra; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p12, 2024)
The value of a firm is often reflected by the well-being of its investors. An increase in firm value not only showcases its current performance but also has significant implications for its future trajectory. This paper seeks to provide empirical evidence regarding the impact of sales growth, profitability, liquidity, and firm size on firm value, guided by signaling theory and pecking order theory. The focus of this study is on firms within the automotive and components subsector listed on the Indonesia Stock Exchange (IDX) over the period from 2019 to 2022. We employed a purposive sampling method to select our samples, which were examined on a quarterly basis, culminating in a total of 112 observations. Our analysis, conducted through multiple regression techniques, indicates that sales growth does not significantly impact the value of a company. However, an increase in profitability correlates with an increase in firm value. Conversely, an increase in both liquidity and firm size appears to negatively affect firm value. These findings underscore the complex interplay between various financial metrics and their influence on a company's market valuation.